Reprint. From: portfolio "Revolučný Odkaz Slovenského Národného Povstania v politickom plagáte" - Spál, Milan, (1974)
Reprint. From: portfolio "Revolučný Odkaz Slovenského Národného Povstania v politickom plagáte".